Numerical study of the active earth pressure distribution on cylindrical shafts using 2D finite difference code - Meftah, Abdelmadjid; Benmebarek, Naïma; Benmebarek, Sadok (Journal of Applied Engineering Science & Technology, 2018)
The present paper examine the distribution of the active pressure on a circular shaft embedded in granular material subjected to radial displacement. The deformation problem was solved under axisymmetric conditions using explicit finite difference code FLAC (Fast Lagrangian Analyses of Continua). Based on the numerical results, the distribution of the active pressure with increasing excavation depth is non-linear for all interface angle of the shaft, for different diameters and height of the shaft also for the all friction angles of the soil. When friction angle of the soil that are less than, or equal to 10° the active pressure is linear. These results are summarized and compared against previously published theoretical solutions and experimental results.